If (sec A +tan A) (sec B+tan B) (sec C+tan C) = (sec A-tan A) (sec B-tan B) (sec C-tan C), prove
that each of the side is equal to 1.
Answers
Answered by
0
Answer:
(sec A +tan A) (sec B+tan B) (sec C+tan C) = (sec A-tan A) (sec B-tan B) (sec C-tan C)=a
(sec A +tan A) (sec B+tan B) (sec C+tan C)=a
multiply by (sec A-tan A) (sec B-tan B) (sec C-tan C) both side
then 1=a (sec A-tan A) (sec B-tan B) (sec C-tan C) first side = 1
similarly another =1
Hence proved
Similar questions
Hindi,
4 months ago
English,
4 months ago
Social Sciences,
4 months ago
Social Sciences,
8 months ago
English,
8 months ago
Math,
1 year ago